L’innovation territoriale au service de l’écologie informationnelle - Charlotte Ullmann (Netcom, 2008)
This article presents some developing concepts concerning a new vision of digital development that includes sustainable development. From a geographical position this article identifies the need to rethink territorial strategies at the global and local geopolitical context, creating bridges between digital innovations and sustainable principles. The first part reflects on concepts concerning new innovative links between ICT and sustainability, which can contribute to new public policies. The second part shows a paradox in the relationship between ICT and sustainability, as threat or an opportunity, and provides examples of real life projects supported by territorial authorities.